Exploring FeSe2 and porous carbon composite as a cost-effective host for Al3+ in aqueous Aluminum ion batteries - Mirzapure, Vinay; Patrike, Apurva; Shelke, V, Manjusha (Electrochimica Acta, 2025)
Aluminum is a high-energy-density material with low cost, making rechargeable aluminum ion batteries (AIBs) a attractive alternative to alkali metal ion batteries. However, the practical development of aqueous AIBs is hindered by limited electrode. Herein, we report FeSe2-decorated porous nitrogen and sulfur-doped carbon spheres (FSPNSCS) as a cathode material for aqueous AIBs, with an emphasis on the reaction kinetics and electrochemical performance. FSPNSCS is synthesized through a hydrothermal approach, confirmed by comprehensive characterizations using X-ray Diffraction for crystalline structure validation and Scanning Electron Microscopy for analyzing composite morphology. Electrochemical properties and kinetics are probed using cyclic voltammetry and galvanostatic charge-discharge tests. Ex-situ XRD reveals a notable peak shift towards higher 2 theta values during discharge, indicating lattice contraction due to Al3+ insertion. Sulfur and nitrogen doping impart elasticity to the lattice structure, enhancing stability during cycling. Ex-situ XPS confirms Al3+ storage and minimal oxide formation, as further supported by microscopic elemental mapping with HRTEM. The FSPNSCS cathode achieves a reversible capacity of 60 mAh g- 1 at a current density of 200 mA g- 1. The system exhibits outstanding cycling stability, retaining over 90 % of its capacity at 500 mA g- 1 over 1000 cycles, highlighting its potential to advance aqueous AIBs for sustainable energy storage.
Keywords: Aqueous aluminum ion battery; cathode material; Electrochemistry; Transition metal selenide